A Comparative Study of Facebook Marketing Practices of Selected Theme Based Restaurants in India - Chandel, Ajay; Sethi, Amit; Mishra, Punam (Indian Journal of Marketing, 2017)
Speculations that the Internet user base in India will reach a whopping number of over 500 million by 2018 - making India the second largest population of Internet users in the world is presenting a myriad of opportunities and threats to businesses in India. The compoundÂ annual growth rate (CAGR) for the digital Ad-spend in India accounted for 25% from financial year 2011 to financial year 2013. Social networking sites like Facebook, Twitter, and LinkedIn have emerged as an interactive means of communication for businesses. With a user base of 100 million in India, Facebook is valuable to any marketer (Singh, 2014). This paper attempted to understand how Facebook pages are being leveraged by selected theme based restaurants in India. The restaurants were chosen on the basis of presence on Facebook, number of likes and visits (people checked in) on Facebook's page, average public reviews, regularity and frequency of posting of content, and â€œcultureâ€ as a common theme from Northern and Western parts of India. The Facebook page posts (content) of these restaurants from their Facebook page presence till January 31, 2015 were collected, analyzed, and compared. These posts were categorized into distinct Facebook marketing practices and then were benchmarked with the global Facebook marketing best practices globally.